Inapplicability of Human Rights: causes and foundations - Narváez Hernández, José Ramón; Rosales, Carlos Manuel (Diritto Pubblico Europeo - Rassegna online, 2022)
The discourse of human rights is validated by the way in which they are understood, protected, and used. However, there are certain cases or circumstances in which the authority may derogate from or violate a paragraph of an international human rights instrument, This paper, therefore, sets out the various reasons for failing to comply or recognize a given human right.